Antidiarrhoeal activity of leaf extract of Moringa Oleifera in experimentally induced diarrhoea in rats - Lakshminarayana M; Shivkumar H; Rimaben P; Bhargava VK (International Journal of Phytomedicine, 2011)
To evalauate the antidiarrhoeal activity of the hydroalcoholic extract of moringa oleifera leaves. The hydroalchoholic extract was evaluated using rodent animal models of diarrhoea like the castor oil and magnesium sulfate induced gastrointestinal motility, in a model of enteropooling induced by the administration of castor oil and PGE2, Charcoal meal test. Acute toxicity and phytochemical constituents were also been evaluated using standardized methods. The results of the present study indicates that the hydroalcoholic extract of moringa oleifera leaves was effective in inducing a significant protection against experimentally induced diarrhoea by castor oil and magnesium sulfate, as evidenced by a decrease in the number of frequency, weight of stools after 4 hours with respect to control. The extract also prevented the enteropooling induced by castor oil and PGE2 at all the doses tested. Acute toxicity studies indicated that the extract is safe till 2500 mg/kg. The antidiarrhoeal activity though, not ascribed to any particular phytochemical present, general tests performed indicated the presence of flavonoids, tannis which were reported to produce antidiarrhoeal activity. These results showed that Moringa oleifera leaves possess anti-diarrheal properties mediated through inhibition of hyper secretion and gastrointestinal motility that substantiate its use in the treatment of diarrhea in traditional medicines or folklore use.